Experimental and numerical study on behaviour of HSFRC overlay strip strengthened flexural deficient RC beams. (1st November 2019) - Banjara, Nawal Kishor; Ramanjaneyulu, K.
Highlights: Hybrid steel fibre reinforced concrete (HSFRC) as a repair material for retrofit of flexural deficient (FD) RC Beams. Analytical formulations for design of HSFRC overlay strip for strengthening of FD beams. Precast HSFRC overlay strips for strengthening of FD RC beams. Efficacy of HSFRC overlay retrofit in enhancing carrying capacity and fatigue life. Numerical models for simulation of HSFRC overlay strengthened beams. Abstract: Reinforcing the concrete matrix using the steel fibres is an efficient technique for improving the mechanical characteristics of the concrete matrix. In the present study, at first, hybrid steel fibre reinforced concrete (HSFRC) consisting of micro- and macro- steel fibres in the fixed ratio of 1:3 in the concrete mixture is developed for repair applications of deficient/damaged reinforced concrete (RC) structures. HSFRC with 1.5% volume fraction of hybrid fibres is used for pre-casting of overlay strips for retrofitting of flexural deficient (FD-30% deficient) beams. Analytical formulations are presented to arrive at thickness and reinforcements of HSFRC overlay strip for the flexural deficient RC beams to reach the required level of load carrying capacity. HSFRC overlay strips are affixed to the bottom surface of flexural deficient RC beams. Experimental studies are carried out on control, flexural deficient and HSFRC overlay strengthened flexural deficient (HSFRC-SFD) RC beams under static and fatigue loading. It is noted that HSFRC overlay strip of 20 mm thickness has improved the ultimate load and fatigue life of flexural deficient RC beam surpassing that of the control beam (without flexural deficiency). Expression relating stress in reinforcement steel and number of fatigue cycles for failure of RC beams is proposed based on experimental data. This study has demonstrated the efficacy of application of HSFRC overlay strip for retrofitting of flexural deficient beams in easier, cost-effective and effective manner.